School ecosystems for the development of children’s creative thought - Hernández Buitrago, Alirio Severo; Hernández Pineda, Luz Mireya (Universidad Pedagógica y Tecnológica de Colombia, 2012)
This paper is based on the development and results of the research project ‘School ecosystems for the development of children’s creative thought’, which has been being implemented under Action Research parameters since 2010. Its purpose is to design and carry out some pedagogical strategies leading to creative thought development in third, fourth and fifth grade children belonging to Technical School Rafael Uribe, Leonera headquarters, in the municipality of Toca, Department of Boyaca. The project is based on the Ecological Model for Human Development formulated by Urie Bronfenbrenner, Eduard de Bono´s creative thought basis, George Polya’s problem solving method, and the Philosophy for Children proposal stated by Matthew Lipman and promoted in Colombia by Diego Pineda. Those approaches are understood as cross-wise themes leading children to a reflection, creation, argumentation, and analysis process when facing the designed settings (ideas inventor, Math and recreation, Technological Curiosity, and Life Crops) established individually in terms of time and actions, which have made possible to transform the ways of thinking and acting of those taking part in the pedagogical process through questions that guide the everyday duties and the scope of education aims.